Totality of evidence in the development of ABP 215, an approved bevacizumab biosimilar - Thomas, Michael; Thatcher, Nicholas; Goldschmidt, Jerome (Immunotherapy, 2019)
ABP 215 (MVASI™) is the first approved biosimilar to Avastin® (bevacizumab). It is approved in the USA and the European Union (EU) for all bevacizumab indications in these jurisdictions except for ovarian cancer in the USA due to orphan drug exclusivity. ABP 215 was shown to be structurally, functionally and clinically (pharmacokinetic, efficacy and safety) similar to the bevacizumab reference product; the pharmacokinetic study was conducted in healthy adult men (n = 202); safety and efficacy were evaluated in patients with advanced nonsquamous non-small-cell lung cancer (n = 642). Together, these results comprise the totality of evidence that provides scientific justification for extrapolation to all approved indications of the reference product and supports the clinical value of ABP 215 as an additional treatment option.
Gesehen am 05.02.2020